2016
DOI: 10.1097/qad.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density decline according to renal tubular dysfunction and phosphaturia in tenofovir-exposed HIV-infected patients

Abstract: Chronic abnormal phosphaturia explains, at least in part, progressive bone loss during TDF therapy. These data suggest that tubular dysfunction leads to an altered equilibrium between phosphataemia, phosphaturia, and bone as mechanism of progressive BMD decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…We observed a significantly higher prevalence of bone disease in patients with signs of KTD when compared with patients without KTD (54,8 vs 27,6%; p = 0.002 ) and a strong association between bone disease an KTD was also confirmed in the multivariable analysis. As previously described in HIV positive patients treated with TDF a strong association was observed between KTD and a lower bone mineral density [21, 22]. In addition the prevalence of bone disease (osteopenia/osteoporosis) such as the prevalence of KTD was similar to previous report by Calmy et al [23].…”
Section: Discussionsupporting
confidence: 89%
“…We observed a significantly higher prevalence of bone disease in patients with signs of KTD when compared with patients without KTD (54,8 vs 27,6%; p = 0.002 ) and a strong association between bone disease an KTD was also confirmed in the multivariable analysis. As previously described in HIV positive patients treated with TDF a strong association was observed between KTD and a lower bone mineral density [21, 22]. In addition the prevalence of bone disease (osteopenia/osteoporosis) such as the prevalence of KTD was similar to previous report by Calmy et al [23].…”
Section: Discussionsupporting
confidence: 89%
“…However, its clinical significance remains unclear because we neither measured ionized calcium nor corrected for hypoalbuminaemia. Although we did not observe TDF use or TDF-induced secondary hyperparathyroidism to be associated with renal phosphate wasting -a potential mechanism of bone demineralization [15,31,32], we could not rule out this condition because we lack information on renal phosphate loss that could be measured in a 24-h urine specimen or calculated as the ratio of renal tubular maximum reabsorption of phosphate to GFR [33].…”
Section: Discussionmentioning
confidence: 90%
“…After a long-term follow-up study, we did not detect the emergency of TDF-resistance-associated variants (rtA194T, rtP177G, and rtF249A) [7, 8], suggesting that this study will provide the basis for changing to a different medication in clinical trials. The research also revealed bone loss caused by proximal tubular dysfunction during TDF therapy [25, 26], so longitudinal follow-up studies are needed.…”
Section: Discussionmentioning
confidence: 99%